Tonsillar pillars suturing: additional benefit to adenotonsillectomy in children with OSAS? A prospective study - Gonçalves, Ana Isabel C. (2020)
Objectives: To evaluate the impact, in the short and medium term, of the tonsillar pillars suturing on the postoperative results of children with sleep disordered breathing submitted to total bilateral adenotonsillectomy.  Material and Methods: Prospective study of children who underwent adenotonsillectomy between January and July 2019 due to adenotonsillar hypertrophy associated with symptoms compatible with obstructive sleep apnea syndrome (OSAS). Children were alternately included in the intervention group (suture of tonsillar pillars) or in the control group (without pillars suturing). The evaluated results consisted in the improvement/resolution of OSAS assessed through the Pediatric Sleep Questionnaire (PSQ), the rate of complications after surgery and the intensity of postoperative pain, assessed using the Wong-Baker Faces Scale and the number of days of analgesia and liquid diet.  Results: Included 50 children, 25 in each group, aged 3 to 17 years old. A statistically significant difference was found between the average total PSQ score at the 1st, 2nd and 6th postoperative months between the 2 groups (1st month: p <0.001; 2nd month: p <0.001; 6th month: p = 0.042), and the control group always had average total scores higher than the intervention group. There was a statistically significant difference between the mean pain intensity on the 1st postoperative day between groups (p <0.001), with a lower mean pain intensity in the intervention group. There was also a significant difference between the average number of days of analgesia and liquid diet in the 2 groups studied (p = 0.004 and p = 0.019, respectively), with the intervention group having the lowest number of days of analgesia and liquid diet. The rate of post-tonsillectomy hemorrhage was 16% in each group.  Conclusions: Our study shows an evident additional benefit of tonsillar pillars suture to adenotonsillectomy in children with OSAS, conferring a significant benefit in the improvement of obstructive sleep pathology, right from the 1st month and remaining in the 2nd and 6th postoperative months. It also showed benefit in the pain intensity assessed on the 1st postoperative day and in the decrease in the number of days of analgesia and liquid diet. No differences were found in postoperative complications between groups.